2022
DOI: 10.32770/jbfem.vol531-46
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Bank Profitability in Indonesia Based on Commercial Bank Business Activities (Buku)

Abstract: This study aims to determine the determinants of the profitability of banks in Indonesia based on the Commercial Group Business Banks (BUKU). Descriptive and verification methods used on secondary form bank that go public in Indonesian Stock Exchange. The dependent variable is Return on Assets (ROA) and the independent variables are Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), Operational Expense of Operating Income (OEOI) and Net Interest Margin (NIM). The results showed that  in BUKU 2, OEOI ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
1
1
0
3
Order By: Relevance
“…It indicates that net interest margin has a positive impact on return on equity. This finding is similar to the findings of Marlina (2022). Similarly, the beta coefficients for capital adequacy ratio are negative with return on equity.…”
Section: Tablesupporting
confidence: 89%
See 1 more Smart Citation
“…It indicates that net interest margin has a positive impact on return on equity. This finding is similar to the findings of Marlina (2022). Similarly, the beta coefficients for capital adequacy ratio are negative with return on equity.…”
Section: Tablesupporting
confidence: 89%
“…Le et al (2022) found that net interest margin had a positive and significant effect on profitability. Similarly, Marlina (2022) concluded that NIM has a positive and insignificant effect on ROA. Likewise, Sukmadewi (2020) stated that net interest margin variables had a positive and significant effect on Return on Assets (ROA).…”
Section: Net Interest Marginmentioning
confidence: 99%
“…Perbankan merupakan sektor industri dalam bidang jasa keuangan yang menguasai setidaknya 80% aset industri jasa keuangan di Indonesia (Marlina, 2022). Sebagai negara yang berkembang, Indonesia tidak dapat lepas dari peran bank dalam meningkatkan pertumbuhan ekonomi (Fauziah & Fadhilah, 2021).…”
Section: Pendahuluanunclassified
“…Berdasarkan penelitian sebelumnya yang dilakukan oleh (Azmy et al, 2019), (Wiranthie & Putranto, 2020), dan (Nasution, 2021) ditemukan bahwa ROA dipengaruhi oleh LDR. Namun, berbanding terbalik dengan hasil penelitian (Marlina, 2022) yang menemukan bahwa ROA tidak dipengaruhi oleh LDR.…”
Section: Gambar 1 Data Persentase Roa Bank Bumnunclassified
See 1 more Smart Citation